2018
DOI: 10.1111/pace.13435
|View full text |Cite
|
Sign up to set email alerts
|

Persistent sex disparities in implantable cardioverter‐defibrillator therapy

Abstract: In this large, outpatient cohort, we have shown that sex differences in ICD therapy continue to exist, but the difference in ICD prevalence by race was attenuated. Dedicated studies are required to fully understand the causes of persistent sex differences in ICD therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…These disparities are in concordance with previous studies which demonstrated race and sex disparities in ICD utilization rates. 31,32 Our study did demonstrate the lower likelihood of arrhythmias in women compared with men, however, the disparity in ICD therapy can be related to other patient-and provider-related factors which needs further studies to fully understand. Bold P values are significant (P <.05).…”
Section: Discussionmentioning
confidence: 65%
“…These disparities are in concordance with previous studies which demonstrated race and sex disparities in ICD utilization rates. 31,32 Our study did demonstrate the lower likelihood of arrhythmias in women compared with men, however, the disparity in ICD therapy can be related to other patient-and provider-related factors which needs further studies to fully understand. Bold P values are significant (P <.05).…”
Section: Discussionmentioning
confidence: 65%
“…The predominance of men in the implanted population was found in other observational and registry studies. 27,28 The cause for this finding is most likely a higher cardiac disease prevalence in men, but this result raises the possibility that ICD therapy might be underutilized in women. Underutilization could be addressed by comparing gender…”
Section: Resultsmentioning
confidence: 99%
“…Despite the overwhelming evidence of the survival benefit of ICDs, several studies have highlighted disparities in ICD implantation among ICD-eligible women and black patients. 6,7,12,13 Cultural differences in preference, and poor communication with physicians, may partially explain these sex-and race-based ICD disparities. 6,7,14 In our study, only a minority of physicians were aware of sex-and race-based differences in patients' perceptions related to ICD implantation and, as a result, modified their SDM approach.…”
Section: Discussionmentioning
confidence: 99%